Effect of bridging units on the detection performance of Cd{P4Mo6}2-based electrochemical sensors for trace chromium(VI) and tetracycline - Xin-Ying Ma; Hao-Xue Bi; Xiu-Juan Zhang; Jing Du; Yuan-Yuan Ma; Zhan-Gang Han (Polyoxometalates, 2025)
Exploring functional electrochemical sensors for the simultaneous detection of inorganic heavy metal ions and organic antibiotic contaminants in aquatic environments is highly significant. In this study, three reduced phosphomolybdates with distinct bridging units were hydrothermally synthesized for electrochemical sensing of trace levels of Cr(VI) and tetracycline (TC). The formulas are (H2bib)2[Cd(H2O)]2[Na(H2O)0.5][Cd(P4Mo6O31H6.5)2]·13H2O (1), (H2bib)2[Cd(bib)(H2O)]2[Cd(P4Mo6O31H7)2]·17H2O (2), and (H2bib)2Cd[Cd(P4Mo6O31H8)2]·13H2O (3) (bib = 4,4'-bis(imidazolyl)biphenyl). In hybrids 1–3, the reduced phosphomolybdate clusters [Cd(P4Mo6O31)2]22− (Cd{P4Mo6}2) feature chain-like configurations bridged by diverse cationic linkers: {[Cd(H2O)]2[Na(H2O)0.5]}5+ unit for 1, [Cd(bib)(H2O)]2+ fragment for 2, and Cd2+ for 3. Hybrids 1–3 exhibit remarkable dual-mode electrochemical responses for Cr(VI) reduction and TC oxidation because of their excellent electrochemical redox properties. The detection limits for Cr(VI) were 18.41 nM for 1, 30.86 nM for 2, and 38.90 nM for 3, with sensitivities of 122.49, 113.95, and 103.19 μA·mM−1, respectively. For TC detection, the detection limits (LODs) were 6.19 nM for 1, 9.90 nM for 2, and 23.52 nM for 3, with sensitivities of 120.84, 105.44, and 95.95 μA·mM−1, respectively. The LODs for Cr(VI) and TC reach the “nanomolar” level. This study offers a potential method for constructing multifunctional electrochemical sensors for detecting environmental pollutants.